Area Estimation of an Object Using Multiple Infrared Scanning Method for Non-vision Robotic System - M. Thamrin, Norashikin; Arif Ashari, Muhamad; ., . (International Journal of Engineering and Technology, 2018)
This paper presents an obstacle detection based on multiple scanning of a non-stationary and discrete sensor for a non-vision robotic navigation system in an unknown environment. In Simultaneous Localization and Mapping (SLAM), complicated computation and expensive equipment are often used by many researchers to obtain an accurate and absolute result. Therefore, in this project, a low-cost and narrowband discrete sensor, namely, an infrared sensor is utilized to visualize the object as well as estimate its dimension and area for accuracy testing. This sensor is mounted on a rotary joint, which is formed by two servo motors, which are served as the vertical and horizontal axes movement during the scanning operation. Then, the scanned data is stored in a database and 2D graphical image of the scanned object based on these detection data are tabulated by using MATLAB 2D scatter plot toolbox. It is found that the multiple scanned data based on the infrared sensor is not suitable for size determination of an object instead it is suitable for object visualization.Â Â